Pembuatan Desain Denah Lokasi di Desa Wisata Kampung Kue Surabaya Pada Kegiatan KKN - Adjar, Dinda Dwi Puspita; Prasetiawati, Fisca Ardi; Pratama, Maulana Rifqi; Azizah, Nurul; Khoirotunnisa, Fani; Wikartika, Ira; Sari, Rafika (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2022)
Tourism is one of the sectors driving the economy that needs to be given more attention in order to develop properly. Kampung Kue Rungkut is one of the villages that has tourism potential and creative economy. Kampung Kue is located around the Special Economic Zone (Kawasan Ekonomi Khusus, KEK) Surabaya, East Java Province. The villagers, most of whom depend on their livelihood by selling cakes, are a hereditary tradition. Through Kuliah Kerja Nyata (KKN) activities, students try to contribute to the development of Kampung Kue tourism by designing a floor plan for the Kampung Kue tourist location. The results of the floor plan design will be printed and placed at several location points to guide and make it easier for visitors and tourists to recognize the tourist location of Kampung Kue. The implementation of the KKN program went well and contributed to developing a tourism village model based on Regional Innovation Capacity which is expected to contribute to development policies and tourism village management.